The Implementation of Biplot and Cluster Analysis to Construct Sustainable Education Policies Toward Technology Literate Society in Indonesia - Pressylia Aluisina Putri Widyangga (Proceeding International Conference on Religion, Science and Education, 2023)
The digital era encourages society, especially the younger generation, to have the ability in developing technology and adapt in the era full of change and uncertainty. To establish a technology literate society in Indonesia, it is necessary to enhance the quality of education. This research aims to analyse the correlation between the competence in using technology, literacy rates, and the education completion level in establishing a technology literate society. Through biplot analysis, it was found that the education completion level, literacy rate, and the percentage of people who are able to use technology has a high positive correlation. Therefore, provinces where society has the capability to develop technology are provinces that have high literacy rates and educational completion level. In addition, using cluster analysis with the average linkage method, provinces in Indonesia are grouped into four clusters based on the erudition regarding technology, where the first cluster consists of five provinces, second cluster with 22 provinces, third cluster with six provinces, and forth cluster with a province, namely Papua. Through biplot and cluster analysis, the government can construct sustainable policies that are right on target based on the problems faced by each province.